2018
DOI: 10.26468/trakyasobed.437704
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Tartişma Beceri̇leri̇ İle İleti̇şi̇m Beceri̇leri̇ Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: ÖZ: Çalışmanın amacı, öğretmen adaylarının tartışma ve iletişim becerileri arasındaki ilişkinin cinsiyet, mezun olunan okul türü, okumakta olduğu bölüm, günlük internet kullanım süresi ve akademik başarı değişkenleri açısından incelenmesidir. İlişkisel tarama modeli kullanılan çalışmada veriler iki ölçek aracılığıyla toplanmıştır. Öğretmen adaylarının tartışma becerileri için Ocak ve Karakuş (2015) tarafından geliştirilen "Öğretmen Adaylarının Tartışma Becerilerine İlişkin Tutum Ölçeği", İletişim becerilerini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Moreover, Kayabaşı (2014) shared the finding that there was no difference among the maojors in terms of acceptance of the principles of democracy by teacher candidates categorized as numerical and verbal fields. Ocak, Karakuş, and Ocak (2018) reported that differences in department did not affect communication skills. On the other hand, Saracaloğlu at al.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Kayabaşı (2014) shared the finding that there was no difference among the maojors in terms of acceptance of the principles of democracy by teacher candidates categorized as numerical and verbal fields. Ocak, Karakuş, and Ocak (2018) reported that differences in department did not affect communication skills. On the other hand, Saracaloğlu at al.…”
Section: Discussionmentioning
confidence: 98%
“…Bu çalışmada erozyon risk alanlarının tespit edilmesi için CBS ve uzaktan algılama tabanında ağırlıklı çakıştırma yöntemi kullanılmıştır. Bu yöntem Dünya'da ve Türkiye'de başta erozyon olmak üzere sel ve taşkınlar (Ocak, 2018;Ocak vd., 2021), heyelanlar (Kale, 2021) gibi birçok mekânsal analizlerde sıklıkla kullanılmaktadır. Bu yöntemde birden fazla kriter (yükselti, eğim, jeoloji, yağış, bitki örtüsü, toprak, arazi kullanımı vs.) analizin yapıldığı ortamın koşulları göz önüne alınarak kriterlerin puanlanıp çakıştırılarak analiz edilmesiyle sonuçlanmaktadır.…”
Section: Materyal Ve Yöntemunclassified
“…Developing the teacher candidates' communication and discussion skills and so that they can use this in the classroom will increase the effectiveness of the education. For this reason, effective communication should be established in educational settings and discussion method should be used within the limitations (Ocak, Karakuş & Ocak, 2018). In their research, Ocak, Karakuş and Ocak (2018) examined the relationship between the communication skills and discussion skills of prospective teachers and concluded that there is a positive significant relationship between communication skills and discussion skills, and communication skills are an important predictor of discussion skills.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, effective communication should be established in educational settings and discussion method should be used within the limitations (Ocak, Karakuş & Ocak, 2018). In their research, Ocak, Karakuş and Ocak (2018) examined the relationship between the communication skills and discussion skills of prospective teachers and concluded that there is a positive significant relationship between communication skills and discussion skills, and communication skills are an important predictor of discussion skills. From this aspect, it can be said that discussion, which is a communication type, is a method that can be used to strengthen students' communication skills.…”
Section: Introductionmentioning
confidence: 99%